Pengaruh Harga dan Promosi Terhadap Keputusan Pembelian Makanan di Barokah Catering 99 Denpasar - Hakiki, Nurul; Dewi , Luh Komang Candra (Jurnal Mosaik Hospitaliti, 2024)
This study aims to analyze the effect of price and promotion on purchasing decisions at Barokah Catering 99 Denpasar. The research used in this study is quantitative research. Respondents of this study were consumers who bought at Barokah Catering 99. The sampling technique used Purposive Sampling. The analysis technique in this study used multiple linear regression analysis. The results of the analysis show that 1) Price has a positive and significant effect on purchasing decisions at Barokah Catering 99, 2) Promotion has a positive and significant effect on purchasing decisions at Barokah Catering 99, 3) Price and promotion have a positive effect on purchasing decisions at Barokah Catering 99. These results mean that the more competitive the price and the more intense the promotion carried out will be able to increase purchasing decisions at Barokah Catering 99.